2014
DOI: 10.12691/education-2-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Academic Dishonesty/ Corruption in the Period of Technology: <i>Its implication for Quality of Education</i>

Abstract: Cheating has reached alarming proportions in all segments, creating widespread cynicism and an erosion of trust. The root of the problem can be found in our schools, where academic dishonesty is rampant. We, academic communities, are in deep trouble if young people, students, maintain these habits as the next generation. The advancement of technologies, such as cell phones, iPods, internets, has broadened the ways by which people can achieve the goal of cheating. Traditional methods of detection may no longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…A high degree of self-reporting has been recordedstudents admit to having been involved in cheatingbut they often do not see it as immoral behavior (Dömeová and Jindrová 2013). Education sciences students also admit to having been involved in cheating (Cummings et al 2002). Frequent selfreporting is a certain indicator that cheating has acquired the status of habitual behavior.…”
Section: Spreading Of Cheating Its Actors and Frequencymentioning
confidence: 99%
“…A high degree of self-reporting has been recordedstudents admit to having been involved in cheatingbut they often do not see it as immoral behavior (Dömeová and Jindrová 2013). Education sciences students also admit to having been involved in cheating (Cummings et al 2002). Frequent selfreporting is a certain indicator that cheating has acquired the status of habitual behavior.…”
Section: Spreading Of Cheating Its Actors and Frequencymentioning
confidence: 99%
“…In Ethiopia, academic dishonesty, in most cases is being manifested in the form of cheating in exams and plagiarism (papers and assignments) (Bachore, 2014(Bachore, : p. 1062). This could include behaviors such as dishonesty off another student's test during an exam, plagiarizing by not citing the author, or damaging equipment so other students would not be able to use it (such tarring parts of the book, writing on it, hiding, stealing (a lecturer from one university was caught stealing books from Addis Abaa University Kennedy Library to satisfy his addiction and sentenced for two years imprisonment).…”
Section: Definition and Forms Of Academic Dishonestymentioning
confidence: 99%
“…In Ethiopia too, academic dishonesty is rising in an alarming rate (Bachore, 2014). One study (Tefera & Kinde, 2009) reported that the perception and actual encounter of teachers of Addis Ababa University and Jimma University School of Business and Economics and education faculty found that (7.2%) respondents reported that they did not encounter students engaged on academic dishonesty, (14.5%) encountered students engaged on academic dishonesty s once, (14.5%) encountered twice, (30.1%) encountered 3 -5 times, (4.8%) encountered 6 -10 times and (25.3%) encountered more than ten times.…”
Section: Prevalence Of Academic Dishonestymentioning
confidence: 99%
See 1 more Smart Citation
“…Moeck (2002) ve Gallant ve Drinan (2006) öğrencilerin kopya çekme sıklığının % 40 ile % 90 arasında değiştiğini belirtirken, Çetin (2007) ise öğrencilerin kopya çekme sıklığının % 40 ile % 88 arasında değiştiğini belirtmektedir. Öğrencilerin kopya çekme davranışları arasında, başkasının kağıdına bakmak (Semerci, 2004;Çetin, 2007;Alkan, 2008), yanındaki ile konuşmak (Semerci, 2004;Çetin, 2007;Yangın ve Kahyaoğlu, 2009), soruları önceden almak (Durmuşçelebi, 2011), küçük kağıtlara kopyalık hazırlamak (semerci, 2004;Tan, 2001), vücudun muhtelif yerlerine yazmak (Selçuk, 1995), duvar ya da sıra üzerine yazmak (Selçuk, 1995;Semerci, 2004;Akdağ ve Güneş, 2002), Sınav kağıdını değiştirmek (Akdağ ve Güneş, 2002), anlaşmalı arkadaş gurupları oluşturmak (Çetin, 2007), sınav anında kitaba veya deftere bakmak (Kaymakcan, 2002;Dam, 2013) gibi klasik yöntemlerinin yanı sıra mobil telefon, walkmen, MP 3 ve internet (Selçuk, 1995;Kaymakcan, 2002;Durmuşçelebi, 2011;Bachore, 2014) gibi dijital teknolojilerden de yararlanmaktadır.…”
Section: Introductionunclassified